Nikki Bado-Fralick, Coming to the Edge of the Circle: A Wiccan Initiation Ritual - Cowan, Douglas E (Pomegranate, 2007)
Nikki Bado-Fralick, Coming to the Edge of the Circle: A Wiccan Initiation Ritual (Oxford and New York: Oxford University Press, 2005), xii + 181 pp. 35.00 (cloth).